Los tópicos en la historiografía sobre la Guerra de la Independencia - Stampa Piñeiro, Leopoldo (Huarte de San Juan. Geografía e Historia, 2006)
The history of Peninsular War, as any other wars, cannot escape to common places, and truisms. The total collapse of the Spanish regular Army, the romantic view on guerrillas or the hatred shared universally by the Spaniards to the French, are the more common among them. Nobody is going to deny that Spanish regular Army was severely knocked down through the war but, but at the same time it should be recognized that determined to fight as it was, the Army was on their feet from the very first moment to the last battle in France. Guerrilleros were far from being such a romantic warriors devoted to the King and the country and ready to any sacrifice and last but not least, war was something more than fighting and soldering. War was plenty of shameful details; bloody affairs, plunder, atrocities committed against the inhabitants..., but on the other hand war gave way to quite a different attitudes and conducts: love, flirting, gallant behaviour and compassion. It is instructive to look rather more closely at the conduct of the armies, the attitude of civilians, and the relations among them, on these occasions. This article is no more than an attempt to summarize of all these complex relations that, no doubt, should be highlighted.